Evaluation of The DKI Jakarta Provincial Athletics Branch Coaching Program Towards PON XXI Aceh-North Sumatra in 2024 - Asmawi, Moch; Widyaningsih, Heni; Setiawan, Iwan; Musa, Mustara (Universitas PGRI Palembang, 2024)
This study aims to evaluate the athletic sports coaching program of DKI Jakarta Province in preparation for PON XXI Aceh-North Sumatra in 2024. The evaluation was carried out using the CIPP (Context, Input, Process, Product) model developed by Stufflebeam. The research method used is qualitative descriptive with a case study approach. Data were collected through in-depth interviews, observations, and documentation studies. The research informants include PASI DKI Jakarta administrators, coaches, athletes, and other related parties. The results of the context evaluation show that the DKI Jakarta athletic coaching program has clear goals and is in line with the province's vision and mission in the field of sports. The input evaluation revealed that there was adequate resource support, both in terms of infrastructure and funding. However, improvements are still needed in the aspect of recruiting talented athletes and developing coach competencies. In the evaluation of the process, it was found that the implementation of the coaching program had been carried out in accordance with the set plan. The training methods applied have followed the latest developments in coaching science. Product evaluation showed an increase in the achievements of DKI Jakarta athletes in various national championships as an indicator of the success of the program. Based on the findings of the research, it can be concluded that the athletics coaching program in DKI Jakarta Province has been running well and showing positive development. However, there are still several aspects that need to be improved to optimize preparations for PON XXI Aceh-North Sumatra 2024. The recommendations submitted include intensifying the talent search program, improving the quality and quantity of coach training, and optimizing the use of technology in the athlete coaching process.